[12(a^2*b)^3*b^2+3a^2(3a^2*b^3-ab^2)]/(3a^3*b^2)

来源:学生作业帮助网 编辑:作业帮 时间:2022/08/08 03:41:03
[12(a^2*b)^3*b^2+3a^2(3a^2*b^3-ab^2)]/(3a^3*b^2)
(a-b)^3+2ab(a-b)

(a-b)^3+2ab(a-b)(a-b)^3+2ab(a-b)(a-b)^3+2ab(a-b)原式=(a-b)[(a-b)²+2ab]=(a-b)(a²-2ab+b²+

18ab(a-b)^2-12a(b-a)^3

18ab(a-b)^2-12a(b-a)^318ab(a-b)^2-12a(b-a)^318ab(a-b)^2-12a(b-a)^318ab(a-b)^2-12a(b-a)^3=18ab(a-b)^2

(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)

(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)(a+2b)(a-2b)+(a-b)(a+b)-2(a-

(a-b)(3ab+2a²b-b³)

(a-b)(3ab+2a²b-b³)(a-b)(3ab+2a²b-b³)(a-b)(3ab+2a²b-b³)原式=a(3ab+2a²

a^3-ab^2 =a (a^2 -b^2) =a(a+b)(a-b)

a^3-ab^2=a(a^2-b^2)=a(a+b)(a-b)a^3-ab^2=a(a^2-b^2)=a(a+b)(a-b)a^3-ab^2=a(a^2-b^2)=a(a+b)(a-b)你给出的分解因

5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)

5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*

-2ab乘以(-a^+6a^b-3a+b)

-2ab乘以(-a^+6a^b-3a+b)-2ab乘以(-a^+6a^b-3a+b)-2ab乘以(-a^+6a^b-3a+b)^是什么意思?

(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg

(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5

已知3a*a+ab-2b*b=0(a不等于0,b不等于0),求a/b-b/a-(a*a+b*b)/ab的值.

已知3a*a+ab-2b*b=0(a不等于0,b不等于0),求a/b-b/a-(a*a+b*b)/ab的值.已知3a*a+ab-2b*b=0(a不等于0,b不等于0),求a/b-b/a-(a*a+b*

(2a-3b)[(a+b)-b(a-3b)]

(2a-3b)[(a+b)-b(a-3b)](2a-3b)[(a+b)-b(a-3b)](2a-3b)[(a+b)-b(a-3b)]原式=(2a-3b)[a+b-ab+3b^2]=2a^2+2ab-2

ab^3+b^2+b-a+1

ab^3+b^2+b-a+1ab^3+b^2+b-a+1ab^3+b^2+b-a+1ab³+b²+b-a+1=(ab³-a)+(b²+b+1)=a(b³

(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b]

(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b](2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b](2/3a)-[2/(a+b)]

(ab(a^-2ab)-a^2b(a-3b))÷(3a^b)

(ab(a^-2ab)-a^2b(a-3b))÷(3a^b)(ab(a^-2ab)-a^2b(a-3b))÷(3a^b)(ab(a^-2ab)-a^2b(a-3b))÷(3a^b)^是什么?

分解因式a(a-b)^3+2a^2(b-a)^2-2ab(b-a)

分解因式a(a-b)^3+2a^2(b-a)^2-2ab(b-a)分解因式a(a-b)^3+2a^2(b-a)^2-2ab(b-a)分解因式a(a-b)^3+2a^2(b-a)^2-2ab(b-a)a

分解因式a(a-b)^3+2a^2(b-a)^2-2ab(b-a)

分解因式a(a-b)^3+2a^2(b-a)^2-2ab(b-a)分解因式a(a-b)^3+2a^2(b-a)^2-2ab(b-a)分解因式a(a-b)^3+2a^2(b-a)^2-2ab(b-a)a

-ab(a-b)^2+a(b-a)^2-a(a-b)^3

-ab(a-b)^2+a(b-a)^2-a(a-b)^3-ab(a-b)^2+a(b-a)^2-a(a-b)^3-ab(a-b)^2+a(b-a)^2-a(a-b)^3-ab(a-b)^2+a(b-a

ab/a+b=3 a-2ab+b/2a-3ab+2b?

ab/a+b=3a-2ab+b/2a-3ab+2b?ab/a+b=3a-2ab+b/2a-3ab+2b?ab/a+b=3a-2ab+b/2a-3ab+2b?ab/a+b=3∴ab=3a+3b(a-2a

(a+b/a-b)²×2a-2b/3a+3b÷ab/a²-b²

(a+b/a-b)²×2a-2b/3a+3b÷ab/a²-b²(a+b/a-b)²×2a-2b/3a+3b÷ab/a²-b²(a+b/a-b

a+3b/a²-b²·a²+2ab+b²/(a+3b)(a-b)

a+3b/a²-b²·a²+2ab+b²/(a+3b)(a-b)a+3b/a²-b²·a²+2ab+b²/(a+3b)(

(a^2+b^2/a^2-b^2-a-b/a+b)除以2ab/(a-b)(a+b)^2,其中a=3-b

("a^2+b^2/a^2-b^2"-"a-b/a+b")除以2ab/(a-b)(a+b)^2,其中a=3-b("a^2+b^2/a^2-b^2"-"a-b/a+b")除以2ab/(a-b)(a+b)